(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Present study was carried out in urban Haryana to knowthe occupational and economic status ofscavengers in Haryana after implementation of the National Scheme ForLiberation And Rehabilitation of Scavengers (NSLRS). The total sample of 415 respondents was selected from Ambala, Kurukshetra,Karnal, Panipat, Sonipat district of Haryana. The list of the respondents was prepared with the help of the listpublished by Scheduled CastesDevelopment Financial Corporation (SCDFC) Haryana. The respondents, as reflected in our sample,exhibit certain characteristics that are peculiar to their degradation andbackwardness in their occupational and economic status. As far as therespondents in our sample are concerned there are three basic elements thatdetermine the economic position of the family: 1. the condition and type ofhouses, 2. their income and 3. Occupation. Results shows that larger percentage of the respondents 56.1%have Brick/stone wall+Tiled Roof type of houses and 64.1% have the size of two roomsand separate kitchen and bathroom and majority of the respondents(51.1%) have annual income up to Rs. 50000/- per annum and maximum people are engaged in the work of sweeping/cleaningoccupation (63.9%) . The difference between past and present occupation shows that only 5.7% respondentleft their traditional occupation i.e. sweeping /scavenging after theimplementation of this scheme.